Comparison of Modern 3D and 2D MR Imaging Sequences of the Wrist at 3 Tesla - Rehnitz, C.; Klaan, B.; von Stillfried, F.; Amarteifio, E.; Burkholder, I.; Kauczor, H. U.; Weber, M. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: To compare the image quality of modern 3 D and 2 D sequences for dedicated wrist imaging at 3 Tesla (T) MRI.Materials and Methods: At 3 T MRI, 18 patients (mean age: 36.2 years) with wrist pain and 16 healthy volunteers (mean age: 26.4 years) were examined using 2 D proton density-weighted fat-saturated (PDfs), isotropic 3 D TrueFISP, 3 D MEDIC, and 3 D PDfs SPACE sequences. Image quality was rated on a five-point scale (0 – 4) including overall image quality (OIQ), visibility of important structures (cartilage, ligaments, TFCC) and degree of artifacts. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) of cartilage/bone/muscle/fluid as well as the mean overall SNR/CNR were calculated using region-of-interest analysis. ANOVA, paired t-, and Wilcoxon-signed-rank tests were applied.Results: The image quality of all tested sequences was superior to 3 D PDfs SPACE (p < 0.01). 3 D TrueFISP had the highest combined cartilage score (mean: 3.4) and performed better in cartilage comparisons against 3 D PDfs SPACE in both groups and 2 D PDfs in volunteers (p < 0.05). 3 D MEDIC performed better in 7 of 8 comparisons (p < 0.05) regarding ligaments and TFCC. 2 D PDfs provided constantly high scores. The mean overall SNR/CNR for 2 D PDfs, 3 D PDfs SPACE, 3 D TrueFISP, and 3 D MEDIC were 68/65, 32/27, 45/47, and 57/45, respectively. 2 D PDfs performed best in most SNR/CNR comparisons (p < 0.05) and 3 D MEDIC performed best within the 3 D sequences (p < 0.05).Conclusion: Except 3 D PDfs SPACE, all tested 3 D and 2 D sequences provided high image quality. 3 D TrueFISP was best for cartilage imaging, 3 D MEDIC for ligaments and TFCC and 2 D PDfs for general wrist imaging.Key points:• 3 D TrueFISP is recommended for cartilage imaging of the wrist at 3 T.• 3 D MEDIC is recommended for ligaments and TFCC.• Robust 2 D PDfs should be used in routine protocols. 3 D sequences may be added depending on the clinical question.• 3 D PDfs SPACE is currently inferior.Citation Format:• Rehnitz C, Klaan B, von Stillfried F et al. Comparison of Modern 3D and 2D MR Imaging Sequences of the Wrist at 3 Tesla. Fortschr Röntgenstr 2016; 188: 753 – 762
Keywords: wrist; hand; 3 Tesla; 3 D imaging; cartilage imaging; MR imaging